Lufthansa: A century of international growth - Stefan Schmid; Zhengtian Xia (ESCP Europe Wirtschaftshochschule Berlin, 2024)
Over the last century, the passenger airline industry has undergone a series of transformations, with Lufthansa being a key player not only in Europe, but also worldwide. This case study traces Lufthansa's development, from its origins up until its current status, and outlines its expansion by adding destinations, its role in establishing the Star Alliance and engaging in joint ventures, as well as its acquisitions and minority stakes in airlines such as Air Dolomiti, Swiss International Air Lines, Austrian Airlines and Brussels Airlines. The case study not only explains Lufthansa's internationalization strategy, but it also discusses its efforts to optimize its portfolio. Finally, the case study ends with the sustainability challenges Lufthansa faces, opening up questions of how the company will address environmental concerns.
Keywords: A20; F23; G34; L21; L22; L25; L93; M16; Q56; 650; Acquisitions; Airline Industry; Case Study; Export; Internationalization; Joint Ventures; Lufthansa; Market Entry; Minority Stake; Passenger Airlines; Portfolio Optimization; Star Alliance; Strategic Alliances; Sustainability